Helsepersonells erfaringer med pasientforløp i kommuner i Vest-Norge - Skorpen, Torill Aarskog; Kvangarsnes, Marit; Hole, Torstein (Nordisk Tidsskrift for Helseforskning, 2017)
Health services in Norway have been described as fragmented with weak coordination between different care levels with respect to patient pathways. The Coordination Reform’s aim was to improve patient pathways and strengthen user participation. The aim of this study was to investigate health personnel ́s experiences with patient pathways in municipalities in Western Norway. A qualitative design was chosen. Six focus group interviews with health personnel working in municipalities in Western Norway were conducted in 2013 and 2014. The interviews revealed that health personnel experienced that local health services gave cohesive patient pathways and strengthened user participation. Cohesive patient pathways and locally adapted pathways were considered important. Coordination and electronic communication between primary and specialist health care services were seen as inadequate. Trust, teamwork, competence and necessary resources were considered vital. Health personnel ́s experiences indicated that the intended aim of cohesive patient pathways near the patient was met.